MANAJEMEN KOLABORASI DALAM RANGKA RESOLUSI KONFLIK DI TAMAN NASIONAL KELIMUTU - Lukita Awang Nistyantara; Sambas Basuni; Rinekso Soekmadi (Media Konservasi, 2011)
The management of Kelimutu National Park (KNP), who applied preservationist paradigm and centralized policy, had caused a conflict of interest among stakeholders. Therefore, the management strategies of the park by co-management approach were needed to conserve the park and resolve the conflict.  The aims of this research were to analyze the application of the principle of co-management at the time, to identify relevant stakeholders, and to determine the management strategies of the park through co-management approach. The results showed that application of the principle of co-management in the Wologai Tengah village fell in the high/good category, while those applied in the Saga village fell in the category of middle. The results also showed that there were 15 (fifteen) stakeholders who were or could be affected by the decisions and the actions of the park’s management.   Based on the expert’s assessment, the cores of the stakeholders were both the park management and the local community. They could influence the successful management of the park. The management strategies of the park was to implement some activities in the following priorities: 1) conduct a continuous meeting among the core stakeholders, provide assistance to increase the community of economic business, and conduct the KNP conservation extension; 2) coordinate stakeholders forum, establish stakeholders agreement, and conduct socialization of the programs.Keywords: co-management, Kelimutu National park, conflict, collaboration management